1980
DOI: 10.1016/0024-3205(80)90384-7
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of the cholecystokinin-gastrin family of peptides in the brain and gut of rat

Abstract: The average levels of CCK-8-and CCK-like peptides présent in aqueous and acidic extracts of the brain of the newborn rat were, respectively, 5.3 and 2.9 pmol/g wet weight. Thèse low levels increased 20-and 10-fold, respectively, so as to attain, at 25-30 days post partum, values comparable to those found in adult brain. There was also a rapid déposition of CCK-gastrin-like peptides in the whole gut between day 20 post coitum and day 10 post partum, when maximal concentrations were attained. Later, less CCK-gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The post-natal development of CCK-like biological activity in the brain reported in this study is similar to previously published reports on the appearance of CCK-like immunoreactivity (Schneider, Monahan & Hirsch, 1979;Noyer et al 1980). Throughout the first two weeks of life there is very little CCK present in the brain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The post-natal development of CCK-like biological activity in the brain reported in this study is similar to previously published reports on the appearance of CCK-like immunoreactivity (Schneider, Monahan & Hirsch, 1979;Noyer et al 1980). Throughout the first two weeks of life there is very little CCK present in the brain.…”
Section: Discussionsupporting
confidence: 92%
“…(Lichtenberger & Johnson, 1974;Larsson et al 1976). One study has investigated the development of CCK/gastrin-like immunoreactivity in both brain and intestine and reported distinct differences between the two tissues (Noyer et al 1980). Unfortunately the antisera used did not distinguish betweek CCK and gastrin.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, several studies have examined the ontogenetic expression of CCK peptides [28][29][30][31][32][33] and CCK mRNA [33,34] in rodent brains. The earlier pep tide studies have, however, used assays that measured only the bioactive, carboxyamidated CCK peptides [28,33].…”
Section: Discussionmentioning
confidence: 99%
“…The earlier pep tide studies have, however, used assays that measured only the bioactive, carboxyamidated CCK peptides [28,33]. Moreover, with a single exception [30], they have studied only whole brain, cerebral cortex and other telencephalic regions, but not the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…The various kinds of fluctuations of peptides in the central and peripheral nervous system during the ontogeny (see ref. 25 for a review) is recently confirmed by radioimmunoassay system (1,5,14).…”
mentioning
confidence: 87%